Shell powder-based high-activity auxiliary cementing material capable of solidifying chloride ions and preparation method of shell powder-based high-activity auxiliary cementing material
Through the coordinated hydration reaction of shell powder, water-quenched blast furnace slag and lithium slag, combined with chemical exciters and surfactants, the problems of low early activity and steel bar corrosion in existing auxiliary gelling materials are solved, and high activity and durability are achieved The shell powder-based auxiliary gelling material improves the performance and application prospects of concrete.
Patent Information
- Application Number
- CN202411069375.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2024-12-27
AI Technical Summary
The existing concrete auxiliary gelling materials have low early hydration activity and long settling time, and industrial solid waste contains adverse components, which limits their large amount of application and performance in concrete and cannot meet the diversity of different needs.
Develop a shell powder-based high-activity auxiliary gelling material to achieve chloride ions through the synergistic hydration reaction of components such as shell, water-quenched blast furnace slag and lithium slag. The generation of curing and hydrating products improves early strength and durability.
It significantly improves the early and late hydration activity of auxiliary gelling materials, enhances the resistance to permeability and durability, solves the problem of steel bar corrosion, and realizes the physical and chemical curing of chloride ions, improving the mechanical properties of concrete.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of civil engineering, and in particular to a shell powder-based high-activity auxiliary gelling material capable of curing chloride ions and a preparation method thereof. Background Art
[0002] As my country's infrastructure construction continues, the consumption of concrete is also increasing. Cement is the key ingredient of concrete and is often considered the glue of concrete. Its manufacture contributes more than 80% of CO2 emissions in concrete production and more than 8% of global anthropogenic CO2 emissions. The cement industry is currently facing the great challenge of reducing its huge carbon emissions to achieve sustainable development. Therefore, creating and developing green, low-carbon and eco-efficient cement types is an urgent task.
[0003] Adding auxiliary cementitious materials to concrete is considered to be an effective way to reduce the amount of cement used in concrete. At present, the auxiliary cementitious materials used more in my country are mainly bulk industrial wastes including fly ash, blast furnace slag, steel slag, desulfurization ash, silica fume, etc. With the development of my country's industrialization process, the above-mentioned high-quality concrete auxiliary cementitious materials have been in short supply in some areas. For large-volume concrete pouring, the addition of auxiliary cementitious materials can not only effectively reduce the hydration heat and prevent cracking of the structure, but also effectively improve the durability of the structure.
[0004] However, the current auxiliary cementitious materials for concrete all have the problems of low early hydration activity leading to poor early strength and long setting time, and the industrial solid waste raw materials contain some components that are unfavorable to the development of concrete performance. The above problems restrict the large-scale application of auxiliary cementitious materials in concrete. In addition, according to different needs, auxiliary cementitious materials for concrete need to show different properties, so single-component auxiliary cementitious materials can no longer meet the requirements at this stage. Therefore, the development of high-performance multi-component auxiliary cementitious materials for concrete is an urgent problem to be solved in the cement concrete industry. It is also an inevitable trend for the cement concrete industry to move towards green, low-carbon and high-performance development in the future. It is also an important means to realize the resource utilization of bulk solid waste, and plays a significant role in the sustainable development of circular economy and energy. Summary of the invention
[0005] The purpose of the present invention is to provide a shell powder-based high-activity auxiliary cementitious material that can solidify chloride ions, and discloses its preparation method and mechanism of action. The present invention develops a high-activity auxiliary cementitious material while efficiently utilizing waste shell resources, utilizing the characteristics of the chemical composition of each component, exerting a coupling effect to convert chloride ions into hydration products Friedel salts, and realizing the solidification of chloride ions. It can also greatly improve durability and anti-permeability, can be applied to the field of hydraulic concrete, and has a prospect of promotion and application.
[0006] A shell powder-based high-activity auxiliary cementitious material with coupling effect, suitable for the field of silicate cement concrete. It includes the following raw materials: 20-40 shells; 10-20 parts of water-quenched blast furnace slag; 10-20 parts of lithium slag; Chemical stimulant 0.4-0.8 parts; 1-2 parts of sulfate component; Grinding aid 0.5-1 part; 0.5-1 part of surfactant; 0.2-0.4 parts of corrosion resistance enhancer; The cement replacement rate of the auxiliary cementitious material is 10%~30%.
[0007] Furthermore, the chemical composition of the shell is mainly composed of CaO with a content of more than 40%, and the mineral composition is mainly dolomite, with a talc content of more than 80%.
[0008] Furthermore, the mineral composition of the water-quenched blast furnace slag is mainly composed of grossamite, pseudowollastonite, pyroxene, and plagioclase, with a content of more than 90%.
[0009] Furthermore, the mineral composition of lithium slag is mainly spodumene, and the content of gibbsite is greater than 80%.
[0010] Furthermore, the chemical activator includes: sodium aluminate, sodium silicate, sodium hydroxide or a mixture of several thereof.
[0011] Furthermore, the sulfate component includes: one or a mixture of dihydrate gypsum, desulfurized gypsum, and phosphogypsum.
[0012] Furthermore, the grinding aid includes: triethanolamine, triisopropanolamine, or a mixture of one or more thereof.
[0013] Furthermore, the surface modifier includes: silane, polyacrylamide, one or a mixture of several thereof, or a mixture of several thereof.
[0014] Furthermore, the corrosion resistance enhancer includes: one or a mixture of diethylene glycol, n-propanol, isopropanol.
[0015] Furthermore, the preparation method comprises the following steps: S1 Firstly, water-quenched blast furnace slag is crushed, screened and impurity-removed to obtain particles of less than 2 mm, and then the material and grinding aid are put into a ball mill and the grinding time is adjusted to grind into fine powder with a specific surface area of 1000-1200m2 / kg.
[0016] S2 crushes, screens, removes sulfur and iron from lithium slag to obtain particles less than 1 mm, then puts the material and grinding aid into a ball mill and adjusts the grinding time to grind into fine powder with a specific surface area of 1000-1300 / m2 / kg.
[0017] S3 washes the shells, removes the debris on the surface, dries at 100±5℃ for 24 hours to remove moisture, calcines at 850-950℃ for 2 hours and crushes them, then puts the materials and grinding aids into a ball mill and adjusts the grinding time to grind into fine powder with a specific surface area of 2000-3000 m2 / kg.
[0018] S4: Add the above-treated shell micropowder, water-quenched blast furnace slag powder and lithium slag powder to the chemical stimulant, sulfate component, surface modifier and corrosion resistance enhancer in the said proportions and mix and grind evenly for 10-30 minutes to obtain the shell powder-based high-activity auxiliary cementitious material that can be cured with chloride ions as described in claim 1.
[0019] The shell powder, water-quenched blast furnace slag and lithium slag selected by the present invention are respectively calcium-silicon-aluminum phase solid wastes. Through the synergistic hydration reaction between the calcium-silicon-aluminum ternary phases, the reaction activity is further improved so that the auxiliary cementitious material has good hydration activity in the early and late stages of hydration, overcoming the problem of low early activity of industrial solid waste as auxiliary cementitious material for concrete. At the same time, the problem of steel bar corrosion caused by the high chloride ion content in shell marine solid wastes used in building materials is solved.
[0020] Shell, one of the main components of the present invention, has a mineral composition mainly of dolomite and talc, and is rich in carbonate phases. In the early hydration reaction, it can provide nucleation sites for the nucleation growth of hydration products. It reacts with C3A in cement and active Al2O3 dissolved in lithium slag and slag to generate hydration products of hemicarbonate aluminate and monocarbonate aluminate, which combine with free chloride ions in shell powder to generate Friedel salt precipitation, so that chloride ions are solidified to generate hydration products.
[0021]
[0022] One of the main components of the present invention is water-quenched blast furnace slag. After high-temperature water quenching, the blast furnace slag contains a large amount of vitreous aluminosilicate, which can provide active SiO2 for the reaction and can react with CaO in the shell powder to generate CSH gel with a low Ca / Si ratio in the early stage. This CSH gel can not only improve the early strength by hardening, but also chemically and physically adsorb the chloride ions dissolved in the shell powder.
[0023]
[0024] One of the main components of the present invention is lithium slag, which contains a large amount of aluminate phase and sulfate phase. In the early stage of hydration, the sulfate phase can generate ettringite to improve the early strength, and the aluminate phase reacts with the carbonate phase in the shell powder to generate carbon aluminate hydration products, and prevents the ettringite from being converted into a monosulfur type sulphoaluminate hydration product, maintaining the stable existence of the ettringite, and the large volume of the hydration product ettringite will cut off the transmission channel of the chloride ions, thereby realizing the physical solidification of the chloride ions.
[0025] The chemical stimulator component, one of the main components of the present invention, mainly acts to increase the alkalinity of the system, accelerate the dissolution of shell powder, water-quenched blast furnace slag and lithium slag, and provide part of silicate ions and aluminate ions to promote the occurrence of hydration reaction and intensify the solidification of chloride ions.
[0026] The sulfate component, one of the main components of the present invention, mainly acts to provide sulfate ions for the system, increase the content of ettringite generated in the early stage of the system, delay the setting time of cement and prevent the flash setting phenomenon.
[0027] The grinding aid component, one of the main components of the present invention, mainly acts on shielding the static charge between powder particles, improving the fluidity of the analysis, and preventing the occurrence of agglomeration.
[0028] The surfactant component, one of the main components of the present invention, mainly acts to increase the amount of trace active components on the surface of the powder, increase the oxide lattice defects, and produce intermediate substances with strengthening effects during the hydration process.
[0029] The corrosion-resistant enhancer, one of the main components of the present invention, mainly acts to enhance the interfacial bonding force and strength between the solid and liquid phases, prevent the concrete from cracking and generating pores, and block the transmission of chloride ions.
[0030] In summary, the auxiliary cementitious material prepared by the present invention using shell powder, water-quenched blast furnace slag, lithium slag and performance improver utilizes the complementarity of the chemical composition and phase composition of the three materials, realizes the solidification of chloride ions through a synergistic hydration reaction, and further improves the mechanical properties under the action of the performance improver. Compared with other industrial solid waste auxiliary cementitious materials, shell powder-based auxiliary cementitious materials generate semi-carbon aluminate and monocarbon aluminate during the hydration process, and calcium sulfonate and low-density CSH gel can realize the physical and chemical solidification of chloride ions. These hydration products can cut off the transmission channel of chloride ions and realize the physical adsorption of chloride ions. Semi-carbon aluminate, monocarbon aluminate and low-density CSH gel can convert chloride ions into Friedel salt precipitates and new CSH gels, realize the chemical adsorption of chloride ions, and can maintain a high activity index at various stages of hydration. DETAILED DESCRIPTION
[0031] The present invention will be further described below in conjunction with examples. It should be noted that the following examples are based on the present technical solution and provide detailed implementation methods and specific operating processes, but the protection scope of the present invention is not limited to these examples.
[0032] The present invention is a shell powder-based high-activity auxiliary cementitious material with coupling effect, which is suitable for the field of silicate cement concrete. It includes the following mass ratios: 20 to 40 parts of shells; 10 to 20 parts of water-quenched blast furnace slag; 10 to 20 parts of lithium slag; 0.4 to 0.8 parts of performance improver, wherein the cement replacement rate of the auxiliary cementitious material is 10 to 30%.
[0033] Preferably, the blast furnace slag has a specific surface area of 1000-1200m 2 / kg of micro powder, the specific surface area of the lithium slag is 1000-1300m 2 / kg of micro powder, the shell powder has a specific surface area of 2000-3000m 2 / kg.
[0034] Chemical composition see Appendix 1: Table 1 <![CDATA[SiO2]]> <![CDATA[Al2O3]]> CaO <![CDATA[SO3]]> MgO Shell powder 16.5% 0.3% 46.6% 0.05% 36.3% Lithium slag 54.5% 25.4% 6.4% 10.2% 0.6% Blast furnace slag 30.7% 15.9% 42.3% 1.8% 6.7% Furthermore, the method comprises the following steps: S1 First, the water-quenched blast furnace slag is crushed, screened and impurity-removed to obtain particles of less than 2 mm, and then the material is put into a ball mill and the grinding time is adjusted to grind into fine powder with a specific surface area of 1000-1200m2 / kg.
[0035] S2 After the lithium slag is crushed, screened, desulfurized and iron removed to obtain particles <1mm, the material is put into a ball mill and the grinding time is adjusted to grind into fine powder with a specific surface area of 1000-1300 / m2 / kg.
[0036] S3 Wash the shells, remove the debris on the surface, dry them at 100±5℃ for 24 hours to remove moisture, calcine them at 850-950℃ for 2 hours, and after crushing, put the materials into a ball mill and adjust the grinding time to grind into fine powder with a specific surface area of 2000-3000 m2 / kg.
[0037] S4 Add the above-treated shell micropowder, water-quenched blast furnace slag powder and lithium slag powder into the performance improver in the stated amount and mix and grind evenly for 10-30 minutes to obtain the shell powder-based high-activity auxiliary cementitious material capable of curing chloride ions as described in claim 1. Example 1.
[0038] 40 parts of shells were cleaned according to the S3 process to remove the surface debris, dried at 100±5℃ for 24 hours to remove moisture, calcined at 850-950℃ for 2 hours, and ground to a specific surface area of 2000-3000m 2 / kg of micro powder. The shell powder mono-system auxiliary gelling material is obtained. Example 2.
[0039] 20 parts of blast furnace slag are crushed, screened and impurity-removed according to the S1 process to obtain particles of less than 2 mm, and then ground and placed in a specific surface area of 1000-1200m 2 / kg of micro powder.
[0040] In the second step, 20 shells were cleaned according to the S3 process to remove the surface debris, dried at 100±5℃ for 24 hours to remove moisture, calcined at 850-950℃ for 2 hours, and ground to a specific surface area of 2000-3000m 2 / kg of micro powder. The two materials are evenly mixed in a ratio of shell powder to blast furnace slag of 1:1 to obtain a shell powder-blast furnace slag binary system auxiliary cementitious material. Example 3.
[0041] 20 parts of lithium slag are crushed, screened, desulfurized and deironized according to the S2 process to obtain particles <1 mm, and then ground to a specific surface area of 10000-13000 / m 2 / kg of micro powder.
[0042] In the second step, 20 shells were cleaned according to the S3 process to remove the surface debris, dried at 100±5℃ for 24 hours to remove moisture, calcined at 850-950℃ for 2 hours, and ground to a specific surface area of 2000-3000m 2 / kg of fine powder. The two materials are evenly mixed in a ratio of shell powder to lithium slag of 1:1 to obtain a shell powder-lithium slag binary system auxiliary gelling material. Example 4.
[0043] 20 parts of water-quenched blast furnace slag are crushed, screened and impurity-removed according to the S1 process to obtain particles <2 mm, and then ground and placed in a specific surface area of 1000-1200m 2 / kg of micro powder.
[0044] In the second step, 20 parts of lithium slag are crushed, screened, desulfurized and deironized according to the S2 process to obtain particles <1 mm, and then ground to a specific surface area of 10000-13000 / m 2 / kg of micro powder.
[0045] In the third step, 40 shells were cleaned according to the S3 process to remove the surface debris, dried at 100±5℃ for 24 hours to remove moisture, calcined at 850-950℃ for 2 hours, and ground to a specific surface area of 2000-3000m 2 / kg of micro powder. The auxiliary cementitious material of shell powder-water-quenched blast furnace slag-lithium slag ternary system is obtained.
[0046] The performance test of the auxiliary gelling material of the above embodiment is as follows: Ordinary silicate P.O42.5 cement was selected as the standard group.
[0047] The activity index test was conducted by replacing 20% of silicate cement with the example, and the activity results are shown in Table 2.
[0048] It can be seen from Table 2 that the early and late activity indexes of the auxiliary cementitious material of Example 4 of the present invention are higher than those of the control group, and it exhibits high activity as an auxiliary cementitious material. In addition, both Example 2 and Example 3 are binary auxiliary cementitious material systems, and their activity indexes are higher than the one-component auxiliary cementitious material system in Example 1, and Example 4 is a ternary auxiliary cementitious material system, and its activity index is higher than the binary auxiliary cementitious material system in Examples 2 and 3. This shows that there is a coupling effect between shell powder, blast furnace slag and lithium slag, and they can be used as high-activity auxiliary cementitious materials for cement concrete. Example 5.
[0049] 20 parts of water-quenched blast furnace slag are crushed, screened and impurity-removed according to the S1 process flow to obtain particles of less than 2 mm, and then ground into fine powder with a specific surface area of 1000-1200m2 / kg.
[0050] In the second step, 20 parts of lithium slag are crushed, screened, desulfurized and deironized according to the S2 process to obtain particles less than 1 mm, and then ground into fine powder with a specific surface area of 10000-13000 / m2 / kg.
[0051] In the third step, 40 parts of shells are washed according to the S3 process, the surface impurities are removed, the shells are dried at 100±5°C for 24 hours to remove moisture, calcined at 850-950°C for 2 hours, and ground into micro powder with a specific surface area of 2000-3000m2 / kg. The shell powder-water-quenched blast furnace slag-lithium slag ternary system auxiliary cementitious material is obtained.
[0052] The performance test of the auxiliary gelling material of the above embodiment is as follows: Ordinary silicate P.O42.5 cement was selected as the standard group.
[0053] The activity index test was conducted by replacing 10% of silicate cement with the embodiment. The results are shown in Table 3. Example 6.
[0054] 20 parts of water-quenched blast furnace slag are crushed, screened and impurity-removed according to the S1 process flow to obtain particles of less than 2 mm, and then ground into fine powder with a specific surface area of 1000-1200m2 / kg.
[0055] In the second step, 20 parts of lithium slag are crushed, screened, desulfurized and deironized according to the S2 process to obtain particles less than 1 mm, and then ground into fine powder with a specific surface area of 10000-13000 / m2 / kg.
[0056] In the third step, 40 parts of shells are washed according to the S3 process, the surface impurities are removed, the shells are dried at 100±5°C for 24 hours to remove moisture, calcined at 850-950°C for 2 hours, and ground into micro powder with a specific surface area of 2000-3000m2 / kg. The shell powder-water-quenched blast furnace slag-lithium slag ternary system auxiliary cementitious material is obtained.
[0057] The performance test of the auxiliary gelling material of the above embodiment is as follows: Ordinary silicate P.O42.5 cement was selected as the standard group.
[0058] The activity index test was conducted by replacing 30% of the silicate cement with the embodiment. The results are shown in Table 3.
[0059]
Claims
1. A shell powder-based high-activity auxiliary gelling material capable of curing chloride ions, characterized in that: The auxiliary gelling material comprises the following raw materials: 20-40 shells; 10-20 parts of water-quenched blast furnace slag; 10-20 parts of lithium slag; 0.4-0.8 parts of chemical stimulant; 1-2 parts of sulfate component; Grinding aid 0.5-1 part; 0.5-1 part of surfactant; 0.2-0.4 parts of anti-corrosion enhancer; The cement replacement rate of the auxiliary cementitious material is 10%~30%.
2. The shell powder-based high-activity auxiliary gelling material capable of curing chloride ions according to claim 1, characterized in that: The shell chemical composition mainly has a CaO content greater than 40%, and the mineral composition mainly has dolomite and a talc content greater than 80%.
3. The shell powder-based high-activity auxiliary gelling material capable of curing chloride ions according to claim 1, characterized in that: The water-quenched blast furnace slag is mainly composed of grossamite, pseudowollastonite, pyroxene and plagioclase, with a content of more than 90%.
4. The shell powder-based high-activity auxiliary gelling material capable of curing chloride ions according to claim 1, characterized in that: The lithium slag mineral composition is mainly spodumene, and the content of gibbsite is greater than 80%.
5. The shell powder-based high-activity auxiliary gelling material capable of curing chloride ions according to claim 1, characterized in that: The chemical stimulant includes: sodium aluminate, sodium silicate, sodium hydroxide or a mixture of the two or more thereof.
6. The shell powder-based high-activity auxiliary gelling material capable of curing chloride ions according to claim 1, characterized in that: The sulfate component includes: one or a mixture of dihydrate gypsum, desulfurized gypsum and phosphogypsum.
7. The shell powder-based high-activity auxiliary gelling material capable of curing chloride ions according to claim 1, characterized in that: The grinding aid comprises: triethanolamine, triisopropanolamine or a mixture of one or more thereof.
8. The shell powder-based high-activity auxiliary gelling material capable of curing chloride ions according to claim 1, characterized in that: The surface modifier includes: silane, polyacrylamide, one or a mixture of several of them, or a mixture of several of them.
9. The shell powder-based high-activity auxiliary gelling material capable of curing chloride ions according to claim 1, characterized in that: The corrosion resistance enhancer comprises: one or a mixture of diethylene glycol, n-propanol, isopropanol.
10. The method for preparing the shell powder-based high-activity auxiliary gelling material capable of curing chloride ions as claimed in claim 1, characterized in that: The preparation method comprises the following steps: S1 First, the water-quenched blast furnace slag is crushed, screened and impurity-removed to obtain particles of less than 2 mm, and then the material and grinding aid are placed in a ball mill to adjust the grinding time and the specific surface area of the grinding mill is 1000-1200m 2 / kg of micro powder. 11.S2 After the lithium slag is crushed, screened, desulfurized and iron removed to obtain particles <1mm, the material and grinding aid are placed in a ball mill and the grinding time is adjusted to a specific surface area of 1000-1300 / m 2 / kg of micro powder. 12.S3 clean the shells and remove the debris on the surface. Dry for 24 hours to remove moisture, calcine at 850-950℃ for 2 hours, and then put the material and grinding aid into a ball mill to adjust the grinding time and grind to a specific surface area of 2000-3000 m 2 / kg of micro powder. 13.S4 Add the above-treated shell micropowder, water-quenched blast furnace slag powder and lithium slag powder into the chemical stimulant, sulfate component, surface modifier and corrosion resistance enhancer in the stated amounts and mix and grind evenly for 10-30 minutes to obtain a shell powder-based high-activity auxiliary cementitious material that can solidify chloride ions.
